The effect of the site of laser zona opening on the complete hatching of mouse blastocysts and their cell numbers - Usanee Sanmee (2018)
© 2016. The Korean Society For Reproductive Medicine. Objective: We studied the effect of the site of laser zona opening on the complete hatching of mouse blastocysts and the cell numbers of the completely hatched blastocysts. Methods: Mouse blastocysts were randomly allocated to the inner cell mass (ICM) group (zona opening performed at the site of the ICM, n=125), the trophectoderm (TE) group (zona opening performed opposite to the ICM, n=125) and the control group (no zona opening, n=125). Results: The rate of complete hatching of the blastocysts was not significantly different in the ICM and the TE group (84.8% vs 80.8%, respectively; p=0.402), but was significantly lower in the control group (51.2%, p < 0.001). The cell numbers in the completely hatched blastocysts were comparable in the control group, the ICM group, and the TE group (69±19.3, 74±15.7, and 71±16.8, respectively; p=0.680). Conclusion: These findings indicate that the site of laser zona opening did not influence the rate of complete hatching of mouse blastocysts or their cell numbers.